PERAN RUTGERS WORLD POPULATION FOUNDATION DALAM MENYEDIAKAN PENDIDIKAN SEKSUAL KOMPREHENSIF BAGI REMAJA DI INDONESIA TAHUN 2018-2021 - Rasyid, Muhammad Irfan; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Comprehensive Sexuality Education (CSE) has become a widely discussed topic due to the increasing discourse of sexuality and gender roles, particularly among adolescents. The provision of comprehensive sexuality education has not been implemented smoothly in several countries. The Rutgers World Population Foundation (WPF) identified existing barriers in Indonesia and sought to assist in delivering comprehensive sexuality education to Indonesian adolescents. This study aims to examine the role of the Rutgers World Population Foundation (WPF) as a Non-Governmental Organization (NGO) in providing sexuality education for adolescents in Indonesia during the period of 2018–2021. Rutgers WPF implemented the Semangat Dunia Remaja (SETARA) program in Bandar Lampung, Denpasar, and Semarang. This research employs a qualitative method, drawing upon the pluralism perspective and the Non-Governmental Organization (NGO) theory developed by David Lewis and Nazneen Kanji. As an NGO, the Rutgers World Population Foundation (WPF) serves as the implementing actor in the Semangat Dunia Remaja (SETARA) program. WPF is responsible for curriculum development, teacher training, and the allocation of financial resources to ensure the sustainability of the program. The intervention of sexuality education through the Semangat Dunia Remaja (SETARA) program has shown varied outcomes in improving the level of sexuality education among adolescents in Indonesia. Keywords: Comprehensive Sexuallity Education, Rutgers World Population Foundation (WPF), Pluralism, Non-Governmental Organization (NGO).